Impact of time of harvest and drying method on antimicrobial activity of Saccharina latissima against two Staphylococcus aureus strains. Issue 1 (1st January 2021) - Cusson, Amber J.; Burkholder, Kristin M.; Byron, Carrie J.; Grebe, Gretchen S.; Deveau, Amy M.
ABSTRACT: Antibiotic resistance is one of the greatest public health threats of our time, and the bacterium Staphylococcus aureus, of which there are numerous drug-resistant and drug-sensitive strains, is a pathogen of worldwide concern. Scientists are turning their focus to underexplored marine ecosystems to identify novel antibacterial agents effective against S. aureus . Here, we report inhibition of S. aureus strains Newman and USA300 by extracts from Saccharina latissima (sugar kelp), grown and harvested in the Western Gulf of Maine, USA. We examined how time of harvest throughout the growing season as well as the drying method pre-extraction affected the antimicrobial activity of the kelp extracts. Optimal antimicrobial activity was observed at the beginning of April (203 days since sporing), when increased water pH and higher salinity levels were also observed. Oven-dried crude extracts showed greater inhibition against S. aureus Newman, whereas freeze-dried crude extracts demonstrated greater inhibition against S. aureus USA300. Overall, our data indicate that cultivated S. latissima from the Western Gulf of Maine possesses significant value-added antimicrobial activity and identify early spring as an optimal harvest time to harness antimicrobial activity.